Hepatoprotective effect of hydromethanolic leaf extract of Musanga cecropioides (Urticaceae) on carbon tetrachloride-induced liver injury and oxidative stress - Nwidu, Lucky L.; Oboma, Yibala I.; Elmorsy, Ekramy; Carter, Wayne G. (Elsevier, 2018)
Objective: Natural antioxidant products are gaining popularity as treatments for various pathological liver injuries. Musanga cecropioides (Urticaceae) leaf extract is used in ethnomedicine for the management of jaundice and other hepatic ailments in Ibibio, Nigeria. This study evaluated the hepatoprotective and antioxidant effects of M. cecropioides hydromethanolic leaf (MCHL) extract against carbon tetrachloride (CCl4)-induced hepatotoxicity in rats. Methods: Liver damage was induced by administering CCl4 dissolved in liquid paraffin (2 mL/kg bw 1:1 intraperitoneally) after pretreatment with MCHL extract for 7 days. Thereafter, acute hepatotoxicity was evaluated in 36 Wistar rats divided into six groups (A–F) of six animals each. Group A served as the negative control; B received CCl4 1 mL/kg only; C–E received 70.7, 141.4, and 282.8 mg/kg MCHL extract, respectively; and F received silymarin 100 mg/kg daily for 7 days by oral gavage. After 48 h, the rats were sacrificed, and samples obtained from them were assayed for histological and biochemical biomarkers of hepatotoxicity. Result: The MCHL extracts significantly (p < 0.001–0.05) reduced the increase in aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), conjugated bilirubin (CBIL), and total bilirubin (TBIL) levels induced by CCl4 intoxication. There was no significant alteration in haematological indices or weight following administration of the MCHL extracts. Histopathological examinations revealed mitotic bodies in the 141.4 mg/kg MCHL extract-treated rats, an indication of tissue repair processes. Conclusion: The MCHL extract has a dose-specific hepatoprotective effect; hence, the utilisation of this extract for the management of hepatitis requires caution.